Growth performance and nutritional condition of marble goby (oxyeleotris marmoratus) larvae fed under different onsets of first feeding - Siti Fairus Mohamed Yusoff; Fui Fui Ching; Gunzo Kawamura; Shigeharu Senoo (Blackwell Publishing Inc., 2023)
Te marble goby (Oxyeleotris marmoratus) is a valuable food fsh, but its aquaculture production is often hampered by poor growth performance associated with starvation at an early stage. Te objective of this study was to investigate the efects of delayed initial feeding on the growth performance and nutritional condition of the marble goby. Six diferent frst feeding times were examined: 0, 12, 24, 36, 48, and 60 hours after the frst feeding (HAFF), and their impacts on growth performances were evaluated based on larval fnal total length (mm) and survival (%), while nutritional condition was evaluated based on body morphometric changes, gut epithelium height (μm), and gut condition. Te experiment was conducted for 15 days. All parameters were measured after larvae were collected at diferent sampling times, except survival and growth, which were measured at the end of the experiment. Te results showed that the onset of the frst feeding was 36 h after hatching (hAh) and that a short delay in the frst feeding by 12, 24, 36, 48, and 60 HAFF signifcantly reduced the growth performance of the larvae and severely afected the larval nutrition condition with noticeable shrinkage in body morphometry and gut epithelium height. Tis study concluded that the onset of frst feeding in marble goby occurs at 36 hAH and that frst feeding beyond 36 hAH signifcantly worsens the nutritional condition and growth performance of the larvae.